Strategy Development of Stroberial Fruit Agrotourism on Serang Village Farmers Income, Purbalingga District - Rachmawati, Dewi; Rusdarti, Rusdarti; Haryati, Y. Titik (Journal of Economic Education, 2019)
Natural potential of strawberry fruit agrotourism are still being developed in order to become the main destination when it comes to Serang Village, Karangreja District, Purbalingga Regency. So, the right strategy for developing Strawberry Fruit Agrotourism and a mature strategy so that development can be realized properly and can have a good influence on the income of strawberry farmers. The research objectives are (1) Identifying internal environmental factors in the development of Strawberry Fruit Agro-tourism. (2) Identifying external environmental factors in the development of Strawberry Fruit Agro-tourism. (3) Analyzing development strategies in Strawberry Fruit Agro-tourism. (4) Analyzing the development strategy of the income of farmers in Strawberry Fruit Agro-tourism in Serang Village, Karangreja District, Purbalingga Regency.The approach in this study is a quantitative approach, this study aims to identify internal and external factors. The focus of this study is the strategy of developing strawberry agro tourism on the income of strawberry farmers who refers to the development strategy which is an internal factor, namely Human Resources (HR), Infrastructure, transportation and promotion. Then on external factors, namely the Government, economic conditions, technology and competitors. Data collection techniques using observation, interviews and questionnaires. The analysis technique in this study used a SWOT analysis. The SWOT matrix results show that Strawberry Fruit Agrotourism is in quadrant II, which means activities to expand the business by building in other locations and increasing the amount of production and adding services. Strawberry fruit agrotourism introduces its potential by promoting it so that it can be recognized by the wider community and can expand tourism transportation services. Suggestions for this research are to enhance good cooperation from the tourism service government and Village-Owned Enterprises (BUMDES) to develop strawberry agro-tourism by implementing and implementing planned programs.